Effect of Spraying Parameters on the Morphology of Spray-Coated Active Layers for Organic Solar Cells - Tahirah Razali, Nur; Kamarudin, Khairunisa; Inaba, Shusei; Yusof, Mahshuri; Weng Leong, Yeng; Vohra, Varun (International Journal of Engineering and Technology, 2018)
Over the past decade, organic solar cells (OSCs) have demonstrated their great potential for the low-cost mass production of renewable energy.Â  However, the conventional active layer deposition technique (spin-coating) is not suitable for mass production due to its incompatibility with the roll-to-roll process. Spray-coating is a promising candidate for in-line production of OSCs but parameters such as distance between the spray nozzle and substrate, applied pressure and number of sprays should be optimized to produce adequate film thickness and morphology. Here, we verified how these processing parameters influence the thin film properties and observed that film thickness increases with decreasing nozzle-substrate distance, increasing number of sprays or applied pressure. The processing parameters were adjusted to produce spray-coated films with similar properties to the spin-coated ones thus confirming that spray-coating could replace spin-coating for mass production of OSC devices.Â Â